Foraging and mating behaviors of Hypsignathus monstrosus at the bat‐human interface in a central African rainforest - Elodie Schloesing; Alexandre Caron; Rémi Chambon; Nicolas Courbin; Morgane Labadie; Roch Nina; Frida Mouiti Mbadinga; Wilfrid Ngoubili; Danficy Sandiala; N’Kaya Tobi; Mathieu Bourgarel; Hélène M. De Nys; et al. (Ecology and Evolution)
Abstract Studying wildlife space use in human‐modified environments contributes to characterize wildlife‐human interactions to assess potential risks of zoonotic‐pathogens transmission, and to pinpoint conservation issues. In central African rainforests with human dwelling and activities, we conducted a telemetry study on a group of males of Hypsignathus monstrosus, a lek‐mating fruit bat identified as a potential maintenance host for Ebola virus. During a lekking season in 2020, we investigated the foraging‐habitat selection and the individual nighttime space use during both mating and foraging activities close to villages and their surrounding agricultural landscape. At night, marked individuals strongly selected agricultural lands and more generally areas near watercourses to forage, where they spent more time compared to forest ones. Furthermore, the probability and duration of the presence of bats in the lek during nighttime decreased with the distance to their roost site but remained relatively high within a 10 km radius. Individuals adjusted foraging behaviors according to mating activity by reducing both the overall time spent in foraging areas and the number of forest areas used to forage when they spent more time in the lek. Finally, the probability of a bat revisiting a foraging area in the following 48 hours increased with the previous time spent in that foraging area. These behaviors occurring close to or in human‐modified habitats can trigger direct and indirect bat‐human contacts, which could thus facilitate pathogen transmission such as Ebola virus.